Subacute fatigue in primary care – two sides of the story. Issue 2 (8th March 2019) - Hulme, Katrin; Little, Paul; Burrows, Abigail; Julia, Anna; Moss‐Morris, Rona
Abstract : Objectives: Fatigue is a common symptom in primary care. Chronic fatigue research highlights the value of preventing chronicity, but little research has investigated the early, subacute stage of the fatigue trajectory (<3 months). We aimed to examine patient and general practitioner (GP) perspectives of subacute fatigue in primary care: (1) to gain a better understanding of fatigue during this stage and (2) to explore how management could be improved. Design: A qualitative study design was used. In‐depth, semi‐structured telephone interviews were conducted with 14 patients and 14 GPs (non‐dyadic), recruited from 19 primary care practices. Methods: Interview transcripts were thematically analysed. Initially, patient and GP accounts were analysed separately, before themes were merged to identify shared and independent perspectives. Results: Three main themes were identified. Within these, subthemes from patients', GPs', or shared patient/GP perspectives emerged. The main themes encompassed the following: (1) Change from normal – the impact of fatigue; (2) The challenges of managing fatigue; and (3) The consultation GPs' knowledge was often not reflected in patients' accounts, even for those reporting positive experiences, suggesting knowledge was not effectively translated. Conclusions: Some findings, such as impact, mirror those described in chronic fatigue. New insights into early‐stage fatigue management also arose, including mismatches in patient and GP perceptions on negative tests and not re‐presenting. These highlight the need for better communication and shared understanding. GPs should pre‐emptively present a biopsychosocial model of fatigue and keep communication channels open, particularly in the light of negative physiological tests. Statement of contribution What is already known on this subject? Patients with chronic fatigue retrospectively report lack of understanding from GPs in early stage of illness. Little research has investigated the early stages of the fatigue trajectory. What does this study add? Consequences of an episode of subacute fatigue are similar to those reported for CFS. There is discordance between GPs' positive view of negative tests and patients' need for explanation of symptoms. The length of appointments is a significant barrier for creating shared understanding.